Textile program students' evaluation of lecturers - ÖZNAZ, DEMET; İŞGÖREN, ERKAN (ELSEVIER SCIENCE BV, 2010)
It is an undeniable truth that, keep up with continuously developing technologies and education techniques is a desire. However, the competence of education staffs which haven't have sufficient structure and haven't been supported with in-service educations was always an argument subject. Students' views have important role at lecturers' performances' evaluation. Lecturers have some concerns about evaluating the education and instruction staff's competence with student surveys. This is because of the thought of students might not answer objectively. The precautions taken during the applying of the surveys can easily pass this problem. In the survey done for this study, the necessary precautions are taken and the students are made to evaluate the lecturers from objective point of view. In this study, the evaluation of Marmara University Vocational School of Technical Sciences Textile Program students about lecturers' teaching method and attitudes are examined. For this reason; a survey is done to the students to evaluate lecturers' attitude, and use of lesson equipment and material. The received data are statistically evaluated by using SPSS program. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Textile-apparel education; lecture teaching method; student views; vocational school